Addressing thresholds in the poetry of Kazem Al-Hajjaj, a semiotic approach (Journal of the College of Basic Education, 2022)
They study is a semiotic approach of the titles ' functions in the texts produced by poet Kadhimal- Hajjaj , The research selects This topic due to The importance of titles and their exceptional effect on the post's texts were investigated on preface and followed by the conclusions of the study . The preface includes an account of the structure and the functions of titles . On the first level , the referential function of titles is studied while the communicative functions are explored on the second level